Connections between eating psychopathology, loneliness, and quality of life: insights from a multi-center study - Todisco, Patrizia; Maragno, Laura; Marzotto, Anna; Mezzani, Barbara; Conti, Fabio; Maggi, Luca; Meneguzzo, Paolo (Frontiers in Psychiatry, 2024)
Background Eating disorders (ED) involve dysfunctional attitudes towards food intake, affecting physical and psychosocial well-being. These disorders significantly impact various domains of life and can lead to a decrease in health-related quality of life (HRQoL). Recent studies emphasize the importance of addressing HRQoL in ED treatment, particularly in the context of social isolation and loneliness, but this aspect is currently poorly evaluated. Methods A sample of 220 people with an ED was enrolled for the study from different centers specialized in the treatment of ED and compared to 151 people from the general population. Different validated questionnaires were used to evaluate eating psychopathology, HRQoL, and loneliness. Partial correlation analyzes adjusted for marital status and regressions were used to evaluate the relationships between constructs and the differences between groups. Results Higher feelings of loneliness were associated with a poorer HRQoL in patients and controls. In the ED group, both loneliness and eating psychopathology were significant predictors of HRQoL. Meanwhile, the duration of the disorder predicted HRQoL specifically in underweight patients, and BMI was a predictor of HRQoL in individuals with normal or above-normal weight. Conclusions These findings highlight the importance of considering both HRQoL and loneliness in EDs, particularly among younger individuals. This approach aligns with the increasing focus on the role of interpersonal relationships in the recovery process. Additionally, the data confirm a link between weight and loneliness, suggesting that this connection, especially the differences between underweight patients and those of other weights, deserves further investigation.